CD8 T-Cell Responses before and after Structured Treatment Interruption in Ugandan Adults Who Initiated ART with CD4 T Cells <200 Cell/μL: The DART Trial STI Substudy. - Serwanga, J; Mugaba, S; Betty, A; Pimego, E; Walker, A; Munderi, P; Gilks, C; Gotch, F; Grosskurth, H; Kaleebu, P (2011)
Objective. To better understand attributes of ART-associated HIV-induced T-cell responses that might be therapeutically harnessed. Methods. CD8(+) T-cell responses were evaluated in some HIV-1 chronically infected participants of the fixed duration STI substudy of the DART trial. Magnitudes, breadths, and functionality of IFN-γ and Perforin responses were compared in STI (n = 42) and continuous treatment (CT) (n = 46) before and after a single STI cycle when the DART STI trial was stopped early due to inferior clinical outcome in STI participants. Results. STI and CT had comparable magnitudes and breadths of monofunctional CD8(+)IFNγ(+) and CD8(+)Perforin(+) responses. However, STI was associated with significant decline in breadth of bi-functional (CD8(+)IFNγ(+)Perforin(+)) responses; P = .02, Mann-Whitney test. Conclusions. STI in individuals initiated onto ART at <200 CD4(+) T-cell counts/μl significantly reduced occurrence of bifunctional CD8(+)IFNγ(+)/Perforin(+) responses. These data add to others that found no evidence to support STI as a strategy to improve HIV-specific immunity during ART.